MEF2C-related epilepsy: Delineating the phenotypic spectrum from a novel mutation and literature review. (April 2019) - Borlot, Felippe; Whitney, Robyn; Cohn, Ronald D.; Weiss, Shelly K.
Highlights: MEF2C-related epilepsy has been poorly described in the literature. Our index case carries an unreported likely pathogenic variant in the MEF2C gene. Literature review shows that febrile seizure is the most common seizure type. Myoclonic, focal-onset, generalized, and atonic seizures have also been reported. EEG is consistently abnormal with polyspikes, multifocal and generalized discharges. Abstract: Purpose: MEF2C-related epilepsy has been poorly described in the literature, despite a consistent MEF2C haploinsufficiency phenotype characterized by severe language impairment and motor delay (MIM# 613443). We aimed to delineate the spectrum of electroclinical manifestations of MEF2C-related epilepsy from an illustrative case and literature review. Methods: A retrospective chart review of our case was performed followed by a literature review on PubMed and OMIM. Publications including patients with MEF2C pathogenic, likely pathogenic variants, or microdeletions without involvement of other genes were selected. Results: The index case is a 2-year-old male with global developmental delay who presented at 7 months with atypical febrile seizures, generalized myoclonias, and focal impaired awareness seizures. Neuroimaging studies were unremarkable and electroencephalograms showed high voltage 200-400uV, 2–2.5 Hz generalized spike-and-waves and polyspikes with alternating frontal predominance, and multifocal spike-and-slow waves. Whole exome sequencing showed an unreported de novo likely pathogenic variant in the MEF2C gene c.236 G > C (p.Arg79Pro). Data from ten additional publications including 22 patients were gathered. From the 23 patients in total, 19 (82%) had seizures. Febrile seizures were most common, but myoclonic, focal-onset and generalized seizures were also reported. Electroencephalogram findings were described in eleven, and nine (82%) showed epileptiform abnormalities. Conclusion: MEF2C-related epilepsy may be described as a spectrum of manifestations including febrile seizures, myoclonia, and focal-onset or generalized seizures. Electroencephalogram is consistently abnormal, showing findings such as background slowing, multifocal and generalized epileptiform discharges and polyspikes. It remains unclear whether most patients are responsive or refractory to treatment with anti-epileptic medications.